Experimental and theoretical studies of ni, pd and pt supramolecular polygons, self-assembled with 4,4´-bipyridine (2013)
Supramolecular polygons and polyhedral have many novel applications such as nanoreactors, molecular nanosensors, Host-guest chemistry, among others. In this work is presented the synthesis, characterization and comparison of supramolecular polygons selfassembled between complexes of type [M(dppe)(TOF)2], which have metal centers in the same group (M = Ni, Pd and Pt) and the organic molecule 4,4'-bipyridine. Analyses by UV -Vis , FT -IR , FT -Raman , 1H- 31P -, 1H COSY-and 19F- NMR, showed that the nickelcontaining complex only formed a square, while the palladium- and platinum-containing complexes formed a triangle–square equilibrium.In addition, PM6 calculations for the supramolecular complexes, considering cationic and neutral systems in the gas phase and in solution, were performed. These results reveal that for the three metals, regardless of the environment, the formation of squares is energetically favored over the formation of triangles. Furthermore, it is observed that the Ni centers favor more the formation of squares, whereas the Pt centers favor it less. These theoretical trends are in good agreement with the experimental results.